Risk of progression to overt hypothyroidism in Indian patients with subclinical hypothyroidism: a prospective observational study - Singh, Shailendra Kumar; Singh, Rina; Kumar Singh, Santosh; Iquebal, Mir Asif; Jaiswal, Sarika; Kumar Rai, Pradeep (International Journal of Advances in Medicine, 2022)
Background: Subclinical hypothyroidism (SCH) is a common endocrine disorder but spontaneous course of SCH in India is lacking. The aim of the study is to determine the spontaneous course of SCH and to identify the risk factors, which enhances the occurrence of overt hypothyroidism (OH). Method: This is a real world prospective observational study. 58 SCH were followed up six monthly for one year to determine the course of SCH. Results: After one year of follow up 11 (18.97%) patients progressed to OH. 37 (63.79%) remained in subclinical hypothyroid category. In 10 (17.29%) patients TSH (thyrotropin) normalized. Rate of progression (odds ratio: 4.58; 95% CI: 1.14, 18.28) was significantly more in anti-thyroid peroxidase (TPO) positive group as compared to anti-TPO negative group. Conclusions: This first data from India clearly shows that SCH has a variable course. Rate of progression to OH is high (18.97%) in Indian SCH patients. In a cohort of 58 patients followed for one year only the presence of anti-TPO antibody was predictive of OH. The initial risk stratification can identify patients with SCH at greatest risk for progression to OH in which treatment is mandatory.